MINAT WIRAUSAHA MAHASISWA PROGRAM STUDI AGRIBISNIS PADA MASA PANDEMI COVID-19 - ihsannudin, ihsannudin; Pratiwi, Nindya Ayu (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Amount 5.73% of the national unemployed are college graduates, and it got worse with 15.6% of layoffs due to Covid-19. This condition can be solved by entrepreneurship initiation for college graduates, especially agribusiness students. This research aims to determine the strategic development of entrepreneur interest for agribusiness students due to the Covid-19 pandemic, through (1) analyzing the entrepreneurship interest of Agribusiness students, (2) analyzing the driving and inhibiting factors of entrepreneurship interest for Agribusiness students. The approach of this research is quantitative with descriptive analysis. The location was in the Agribusiness department Faculty of Agriculture, University of Trunojoyo Madura. The results show entrepreneurship interest of Agribusiness students is high. Personal characteristics, business knowledge/skills, and social environment were identified as inhibiting factors for entrepreneurship interest, and the driving factor was the family environment. Academic activity strategies need to be carried out by developing entrepreneurship courses, entrepreneurship curriculum development and adapting materials according to the needs of new entrepreneurs. Meanwhile, non-academic strategies are carried out by increasing participation in PKM and entrepreneurship competitions through incentives, requiring participation in entrepreneurship courses in a pleasant atmosphere, writing training/seminars, and other entrepreneurial activities.